“Tem que conversar, senão não vende, né?”: a inserção de imigrantes senegaleses no comércio de rua de Santa Maria (RS) - Césaro, Filipe Seefeldt de (2018)
This work focuses on international migration, outlining as its focus of study the practice of street sales by Senegalese immigrants in Santa Maria. Favoring every day social interactions in which this group is involved in the city and in view of the tactics that it employs to assure its position in front of the other actors that occupy the same commercial space, this research tries to provide an answer to the following question: in what way have the Senegalese migrants been inserted in the street commerce of the city of Santa Maria (RS)? The general objective is to understand how Senegalese immigrants handled, during the period in which the empirical investigation was carried out (between August 2016 and December 2017), their entry into a space of established social relations. The specific objectives are: (i) to contextualize the Senegalese emigration, the consolidated street sale in the city and this research, (ii) to describe the sales techniques used by Senegalese street vendors in Santa Maria, and (iii) to describe the tactics of political positioning of these individuals in the space of the street commerce of the city. The perspective of “ethnographic doing” was used in order to carry out these tasks. It is therefore possible for the researcher to have contact with both the points of view of the Senegalese themselves about their work and of the actors who move at different levels through the same environment. The empirical data results from the observation of the techniques used in sales situations by the Senegalese, the regularities of their contact with clients and the movements they use in everyday life, as well as informal participation in these negotiating circumstances and in conversations with individuals known by the immigrants at each point of sale used. In addition, semi-structured interviews were used as secondary means of empirical investigation. The text is divided into three main chapters, besides the introduction and final considerations. The first chapter, entitled “From International Relations to Anthropology: context, trajectory and perspectives of an ethnography of the Senegalese street sale in Santa Maria (RS)”, discusses in its three sections the spatio-temporal characteristics of the research itself, the paths traversed by the researcher until the arrival to the object of research and ethnography, and the course undertaken in the process of the field work consolidation. The second chapter, called “‘What’s up, bro!’: Techniques and positions of a selling knowledge”, is divided into two sections that focus on the Senegalese learning of the selling practice in the city, respectively analyzing which logics of body performance and sociability limited to the moments of sale permeate the Senegalese-customers relationship. The third chapter, entitled “To be, to stay and being able to in the sidewalks of sales”, is also divided into two sections, focused on the knowledge and displacements undertaken in/between the points of sale, as well as in the mode of justification of the trade and the sociability lived outside of the moments of commercial negotiation in each stretch of sidewalk they occupy. Keywords: Senegalese immigrants. Street trade. Social interaction.